Impact of obesity on semen quality in men of infertile couples: a cross-sectional study in a tertiary care centre - Rajamanickam, Saranya; Nichanahalli, Kubera S.; Chaturvedula, Latha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Obesity is an emerging problem worldwide. The aim of the study was to determine the association of Body mass index and central obesity with semen parameters in men of infertile couples. Methods: This was a descriptive study conducted in a population that included 219 men of infertile couples who attended the infertility clinic. A detailed history was taken from the participants and measurements of height, weight, waist circumference and hip circumference were done by standard methods. General, systemic and urogenital tract examinations were done. The participants were advised to collect semen specimens and semen was analyzed and various semen parameters were noted based on WHO criteria 2010. Results: Among the overweight and obese men, 12.7% and 20.5% were oligozoospermic respectively. Asthenozoospermia was seen in 21.2% and 25% of overweight and obese men. Among men with waist circumference ≥102 cm, 14.3% had oligozoospermia and 35.7% of men had asthenozoospermia. Around 12.2% of men with a Waist-hip ratio >0.9 had oligozoospermia and 19.8% of them had asthenozoospermia. Conclusions: A significant negative association was seen between WHR and sperm concentration, total sperm count, total progressive motility and total motility were seen to be removed. There was no significant association between WC, BMI and sperm concentration, total sperm count, total progressive motility, and total motility.